Barricades and banners : the Revolution of 1905 and the transformation of Warsaw jewry - Ury, Scott (Stanford, Calif. : Stanford University Press, 2012)
This book examines the intersection of urban society and modern politics among Jews in turn of the century Warsaw. By focusing on the tumultuous events surrounding the Revolution of 1905 'Barricades and Banners' argues that the metropolitanization of Jewish life led to a need for new forms of community and belonging.
Introduction : between past and present -- Warsaw before 1905 : one city, many stories -- Urbanization, community, and the crisis of modernity : Jewish society in turn-of-the-century Warsaw -- Revolution, Jews, and the streets of Warsaw : between secret cells and popular politics -- The rise of the Jewish public sphere : coffeehouses, theaters, and newspapers -- From public sphere to public will : the elections to the Russian State Duma and the politicization of ethnicity -- Democracy and its discontents : the image of "the Jews" and the transformation of Polish politics -- Conclusion : Politics, order, and the dialectics of Jewish modernity.
Includes bibliographical references (pages 365-400) and index.
English.
JSTOR
Keywords: Jews -- Poland -- Warsaw; Russia -- History -- Revolution, 1905-1907.; Juifs -- Pologne -- Varsovie; Russie -- Histoire -- 1905-1907 (Révolution); SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; HISTORY / Jewish; Jews; Poland -- Warsaw; Russia; 1905-1907; History